Does the European Marriage Pattern Explain Economic Growth - Tracy Dennison; Sheilagh Ogilvie (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper scrutinizes the recently postulated link between the European Marriage Pattern (EMP) and economic success. A metastudy of the historical demography literature shows that the EMP did not prevail throughout Europe, its three key components did not always coincide, and its more extreme manifestations were associated with economic stagnation rather than growth. There is no evidence that the EMP improved economic performance by empowering women, increasing human capital investment, adjusting population to economic trends, or sustaining beneficial cultural norms. European economic success was not caused by the EMP and its sources must therefore be sought in other factors.
Keywords: J12; J13; K00; N33; O17; 330; European Marriage Pattern; nuptiality; household structure; population growth; women; human capital; culture; institutions